Product and Service Design Analysis Case Study - Syahreza Daulay, Ibnu; Gunawan Putra, Erik; Gilang Putra Abdi; Imam Abdul Salam; Aulia Riski Ilahi (Journal of Multidimensional Management, 2024)
Product and service design is important in determining a business's sustainability and success amid increasingly fierce market competition. In the context of the café industry, unique, attractive, and effective design plays a role in meeting customer needs and desires and building strong competitiveness. This research aims to examine the role of product and service design in improving operational efficiency and customer appeal, focusing on a case study of a café. The research uses a qualitative method, where data is obtained through direct observation and interviews with the cafe manager. The results showed that well-designed product and service design can improve customer experience, strengthen loyalty, and extend the business life cycle. Innovation-oriented design and customer needs have proven effective in the face of intensifying competition. In addition, the study also highlights the importance of technology integration in café design to improve operational efficiency. The findings provide practical insights for café owners and other business actors on utilizing design as a strategic tool to achieve sustainable business success and growth.